James Edward Runcie papers - Runcie, James Edward, 1858-1933.
Correspondence, invoices, office memoranda, and inventory lists relating primarily to Runcie's land holdings in Cuba and to finances and politics there. Correspondents include E. H. Crowder, Clarence Ransom Edwards, Edward Singleton Holden, James Luther Slayden, and Oswald Garrison Villard.
In part, transcripts.
U.S. Army officer and lawyer.
Collection material in English.
Keywords: Crowder, E. H. -- 1859-1932 -- Correspondence; Edwards, Clarence Ransom, -- 1860-1931 -- Correspondence; Holden, Edward Singleton, -- 1846-1914 -- Correspondence; Slayden, James Luther, -- 1853-1924 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Finance, Public -- Cuba; Land tenure -- Cuba; Cuba -- Politics and government; Army officers; Lawyers